Long-term survival of a patient with locally advanced hilar cholangiocarcinoma (Klatskin tumor): a case report and review on high level evidence - Vahedian, Jalal; Babaei, Mohammad Reza; Zare Mehrjardi, Ali; Almasi, Ali; Ahmadi, Seyyed Amir Yasin; Hadizadeh, Omid (Archive of Oncology, 2019)
Cholangiocarcinoma, malignant tumor of epithelial cells of bile ducts has poor overall survival and prognosis. We report a case of non-resectable cholangiocarcinoma with a 57-month survival after incomplete R2 surgical margin resection of the tumor. A 52-year old man with generalized itching, jaundice, brownish urine, mild abdominal pain and weight loss of 8 kg in last two months presented. Imaging and surgical workups showed hilar cholangiocarcinoma (Klatskin tumor). Along with incomplete R2 margin resection we performed stent embedding and post-operative adjuvant chemotherapy. Based on current literature data there is no superiority of adjuvant chemotherapy after complete R0 resection compared to incomplete R2 resection. However, it seems that partial resection along with stent embedding and applied adjuvant chemotherapy in cases of locally advanced non-resectable cholangiocarcinoma may increase survival rate.
Keywords: Survival; Stents; Cholangiocarcinoma